Dairesel agregalı model boşluklu betonların dinamik davranışının sonlu eleman yöntemi ile analizi - Ağar Özbek, Ayda Şafak; Weerheijm, Jaap; Breugel, Klaas (Uludag University Journal of the Faculty of Engineering, 2018)
Le béton poreux est un type spécial de béton qui comprend une grande quantité de pores d'air de taille méso et qui est formé par les particules d'agrégats assemblées par une fine couche de pâte de ciment. Dans le cadre d'un projet de recherche, ayant pour objectif de concevoir des bétons poreux à résistance accrue destinés à être utilisés dans des applications de sécurité, les propriétés dynamiques des bétons poreux ont été analysées par la méthode des éléments finis. Dans les analyses, les bétons poreux avec des agrégats circulaires ont été analysés en utilisant la technique d'intégration directe explicite mise en œuvre dans ABAQUS/Explicite. Sur la base des résultats de l'analyse, les vitesses de propagation des ondes de contrainte des bétons poreux et d'un béton ordinaire ont été estimées sur la base du contour de contrainte. Les valeurs estimées numériquement se sont avérées très proches des valeurs de référence dans la littérature et des résultats expérimentaux. D'autre part, les résistances aux chocs obtenues pour deux bétons poreux modèles ayant des tailles d'agrégats différentes se sont avérées être presque égales. Lorsque les distributions de dommages calculées et les concentrations de contraintes ont été examinées, il a été constaté que sous charge dynamique, les fragments se sont formés approximativement à la taille d'agrégats. Au préalable, il est conclu que la taille des fragments dans les bétons poreux est principalement déterminée par la taille des agrégats incorporés dans le mélange.

El hormigón poroso es un tipo especial de hormigón que incluye una alta cantidad de poros de aire de tamaño meso y está formado por las partículas de agregado ensambladas por una capa delgada de pasta de cemento. En el ámbito de un proyecto de investigación, que tiene como objetivo diseñar hormigones porosos de mayor resistencia para ser utilizados en aplicaciones de seguridad, se analizaron las propiedades dinámicas de los hormigones porosos con el método de elementos finitos. En los análisis, se analizaron hormigones porosos con agregados circulares utilizando la técnica de integración directa explícita implementada en ABAQUS/Explícito. Con base en los resultados del análisis, se estimaron las velocidades de propagación de la onda de tensión de los hormigones porosos y un hormigón liso en función del contorno de tensión. Se encontró que los valores estimados numéricamente estaban muy cerca de los valores de referencia en la literatura y los resultados experimentales. Por otro lado, se encontró que las resistencias al impacto obtenidas para dos hormigones porosos modelo que tenían diferentes tamaños de agregado eran casi iguales. Cuando se examinaron las distribuciones de daño y las concentraciones de tensión calculadas, se vio que bajo carga dinámica, los fragmentos se formaron aproximadamente al tamaño De antemano, se concluye que el tamaño de los fragmentos en los hormigones porosos está determinado principalmente por el tamaño de los áridos incorporados en la mezcla.

Porous concrete is a special type of concrete that includes a high amount of meso-size air pores and is formed by the aggregate particles assembled by a thin layer of cement paste. In the scope of a research project, having an objective of designing enhanced strength porous concretes to be used in safety applications, dynamic properties of porous concretes were analyzed with finite element method. In the analyses, porous concretes with circular aggregates were analyzed by using the explicit direct integration technique implemented in ABAQUS/Explicit.Based on the analysis results, stress wave propagation speeds of porous concretes and a plain concrete were estimated based on stress contour.The numerically estimated values were found to be very close to the reference values in the literature and the experimental results.On the other hand, the impact strengths obtained for two model porous concretes having different aggregate sizes were found to be nearly equal.When the computed damage distributions and stress concentrations were examined, it was seen that under dynamic loading, the fragments were formed approximately at the size of aggregates. Beforehand, it is concluded that the fragment size in porous concretes is mainly determined by the size of the aggregates incorporated in the mixture.

Porous concrete is a special type of concrete that includes a high amount of meso-size air pores and is formed by the aggregate particles assembled by a thin layer of cement paste.In the scope of a research project, having an objective of designing enhanced strength porous concretes to be used in safety applications, dynamic properties of porous concretes were analyzed with finite element method.In the analyses, porous concretes with circular aggregates were analyzed by using the explicit direct integration technique implemented in ABAQUS/Explicit.Based on the analysis results, stress wave propagation speeds of porous concretes and a plain concrete were estimated based on stress contours.The numerically estimated values were found to be very close to the reference values in literature and the experimental results.On the other hand, the impact strengths obtained for two model porous concretes having different aggregate sizes were found to be nearly equal.When the computed damage distributions and stress concentrations were examined, it was seen that under dynamic loading, the fragments formed were approximately at the size of aggregates.Therefore, it is concluded that the fragment size in porous concretes is mainly determined by the size of the aggregates incorporated in the mixture.

الخرسانة المسامية هي نوع خاص من الخرسانة يتضمن كمية عالية من مسام الهواء متوسطة الحجم وتتكون من جزيئات الركام التي يتم تجميعها بواسطة طبقة رقيقة من معجون الأسمنت. في نطاق مشروع بحثي، بهدف تصميم خرسانة مسامية معززة القوة لاستخدامها في تطبيقات السلامة، تم تحليل الخصائص الديناميكية للخرسانة المسامية بطريقة العناصر المحدودة. في التحليلات، تم تحليل الخرسانة المسامية ذات الركام الدائري باستخدام تقنية التكامل المباشر الصريحة المنفذة في ABAQUS/صريح. استنادًا إلى نتائج التحليل، تم تقدير سرعات انتشار موجة الإجهاد للخرسانة المسامية والخرسانة العادية بناءً على محيط الإجهاد. تم العثور على القيم المقدرة عدديًا قريبة جدًا من القيم المرجعية في الأدبيات والنتائج التجريبية. من ناحية أخرى، تم العثور على نقاط قوة التأثير التي تم الحصول عليها لنموذجين من الخرسانة المسامية ذات أحجام زلط مختلفة متساوية تقريبًا. عندما تم فحص توزيعات الضرر المحسوبة وتركيزات الإجهاد، لوحظ أنه في ظل التحميل الديناميكي، تم تشكيل الشظايا تقريبًا بالحجم من الركام. قبل ذلك، يتم استنتاج أن حجم الشظية في الخرسانة المسامية يتم تحديده بشكل أساسي من خلال حجم الركام المدمج في الخليط.
Keywords: Physics; Finite Element Analysis; Mühendislik; Building and Construction; Fiber-Reinforced Polymer Composites in Construction; Progressive Collapse of Structures; Fracture Mechanics Modeling and Simulation; Engineering; Mechanics of Materials; Physical Sciences; FOS: Mathematics; Boşluklu beton; Açık sonlu eleman analizi; Dinamik analiz; Porous concrete; Explicit finite element analysis; Dynamic analysis; Drop weight impact test; Durability Performance; Mathematics; Civil and Structural Engineering